2001
DOI: 10.1159/000047609
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Education Improves Stroke Knowledge

Abstract: Background and Purpose: Despite advances in stroke therapy, the public remains uninformed about stroke, and few stroke patients present to the hospital in time to receive treatment. Health education campaigns can increase community awareness and may decrease time to hospital presentation among stroke patients. Methods: We conducted a community-based education campaign utilizing television and newspapers to inform the residents of King County, Wash., USA, about stroke and the need to call 911. The effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
2
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 42 publications
6
112
2
6
Order By: Relevance
“…We found that 84.3% of patients spontaneously named at least one risk factor while most studies reported percentages that range 40 to 79% [13,16,18,20,[32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We found that 84.3% of patients spontaneously named at least one risk factor while most studies reported percentages that range 40 to 79% [13,16,18,20,[32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, only 69.5% would activate emergency medical service. Becker [36] and Rowe [49] have reported very similar results concerning intended activation of emergency medical service, though several other authors have found better results reporting percentages of subjects seeking emergency medical care that range from 72 to 90% [13,18,25,35,50,63,64].…”
Section: Discussionmentioning
confidence: 96%
“…17 The health belief model has been adapted to incorporate a broader range of predictive variables, including demographics, socio-psychological factors, health motivation, and perceived control. 18 Therefore, the purpose of this study was to examine CCs' knowledge of stroke, their lifestyle-related health behaviours and beliefs, and potential relationships among these factors. This research constitutes an important step toward preventing and managing stroke (and possibly other lifestyle-related conditions common in Western cultures) among Chinese immigrants to Canada.…”
Section: Ré Sumémentioning
confidence: 99%
“…Reasons for this shortcoming include poor awareness of stroke signs by the victim or family with inappropriately planned action on seeking immediate medical help, and not perceiving stroke as an emergency by medical personnel 15,[27][28][29] . These facts emphasize the need for continuous education, especially through mass media campaigns.…”
Section: Educationmentioning
confidence: 99%